PENGARUH METODE MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V DI SDN 12 AMPENAN TAHUN AJARAN 2021 - Dwi Dinawan Saputra; Muhammad Tahir; Ida Ermiana (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This study aims to determine the effect of the Talking Stick learning model method on the science learning outcomes of class V students at SDN 12 Ampenan. This study used a quantitative approach with the Quasi Experimental Research method with the pre-experimental research design type one group pretest-posttet design. The population in this study were students of grade V SD with a total of 24 students. The sampling technique used purposive sample with a sample size of 22 students. Data collection techniques in this study using multiple choice test questions and documentation. The data analysis technique used is the t test with the type of paired sample t-test. The results of hypothesis testing show the sig. (2-tailed) the science learning outcomes of students have the same value, namely 0.000 at the 5% significance level with the number N = 22. The sig. (2-tailed) value indicates that there is a significant effect of the Talking Stick method on the science learning outcomes of grade V students at SDN 12 Ampenan in academic year of 2021